Stories from Pacific Island nurses : why do Pacific Island Bachelor of Nursing students not return to their own countries after being scholarship recipients? : thesis in partial completion of the requirement for the Master of Education, Massey University, Wellington - Stewart, Felicity (Massey University, 2004)
"O le tele o sulu e maua ai figota o le sami" This Samoan proverb means the more torches/lights used, the more shellfish you can find. The more ideas and suggestions that people contribute; will help to shed light on challenges that are faced. The light shed by this research will assist in the resolution of some challenges for future Pacific Island nurses. There are many challenges that face students who study in a country other than their own with the expectation that they will subsequently return to their own home and utilise the skills and knowledge that they have gained. The nurses who are participants in this research were studying in a Bachelor of Nursing (BN) programme in a Polytechnic in New Zealand. They were students between the years 1998-2002. The students were supported in their education through Aotearoa scholarships, which are administered in New Zealand as part of the aid and development budget. Many of these students do not return to their own countries after completion of their studies (Personal communication New Zealand Agency for International Development [NZAID] personnel, June 2003., Davenport & Low, 2004). I wanted to know what the reasons were. The focus of this research is the stories of five scholarship recipients. [FROM INTRO]
Keywords: New Zealand; Nursing students -- Attitudes; Minorities in nursing; Pacific Islanders -- Education (Higher)